Impact of metabolic-associated fatty liver disease on the cholesterol efflux capacity of high-density lipoproteins in adolescents with type 2 diabetes - José Antonio Orozco Morales; José Antonio Orozco Morales; Aída Xochitl Medina Urrutia; Margarita Torres Tamayo; Margarita Torres Tamayo; Juan Reyes Barrera; Esteban Jorge Galarza; Juan Gabriel Juárez Rojas; Pilar Dies Suarez; Nahum Méndez Sánchez; Nahum Méndez Sánchez; Luis Enrique Díaz Orozco; et al. (Frontiers in Pediatrics)
ContextType 2 diabetes (DM2) is an emerging disease in the pediatric population. DM2 is associated with metabolic-associated fatty liver disease (MAFLD). High-density lipoproteins (HDLs) are lipoproteins that are believed to have atheroprotective properties that reduce the risk of cardiovascular disease (CVD). Current evidence suggests that the physicochemical and functional features of HDLs may play a key role in the pathogenesis of atherosclerosis.ObjectiveWe aimed to assess the impact of MAFLD on cholesterol efflux capacity (CEC) in adolescents with DM2.DesignA cross-sectional study.SettingAttention clinic for Children with Diabetes of the Hospital Infantil de México Federico Gómez.Patients or other participantsThis study included a total of 70 adolescents, 47 of which had DM2 and 23 were healthy individuals.InterventionsThe presence of MAFLD was determined by MR spectroscopy with proton density fat fraction. We compared the distribution of HDL subtypes (HDL2b, HDL2a, HDL3a, HDL3b, and HDL3c) and the chemical composition of HDLs (total protein, triglycerides, phospholipids, cholesteryl esters, and free cholesterol). HDL functionality was determined by the CEC, measuring the fluorescent cholesterol efflux from J774 macrophage cells.Main outcome measuresWe were expecting to observe a decrease in HDL efflux capacity in adolescents with type 2 diabetes and MAFLD.ResultsIn our study, we observed a prevalence of MAFLD in 66% of adolescents with DM2, similar to that reported in other international studies (60%–80%). In the population with DM2 and MAFLD, we did not observe a decrease in CEC. Initially we found a slight elevation of CEC in adolescents with DM2, however, with the increase in liver fat, a little decrease is observed, which could explain a probable metabolic phenomenon, since the physicochemical composition and distribution of the particles is associated with the percentage of liver fat. A positive correlation between the percentage of liver fat and the concentration of HDL2b (p = 0.011), HDL2a (p = 0.014) and average particle size (p = 0.011) and the proportion of triglycerides inside the particles (p = 0.007). Likewise, negative correlation were found with the percentage of liver fat, cholesterol esters (p = 0.010) and free cholesterol of the particles (p < 0.001). We observed a positive correlation between CEC and the percentage of triglycerides (p = 0.007), and a negative correlation with the percentage of cholesterol esters (p = 0.05) inside the HDL's particles.ConclusionsIn this group of adolescents with DM2, the presence of MAFLD was not associated with CEC; however, it is associated with abnormalities in the distribution and lipid composition of HDL particles. The momentum generated by the original proposal for MAFLD in the adult population and following the recommendations for pediatric MAFLD will be a step forward in helping to study the impact of MAFLD on the atheroprotective properties of HDL in the pediatric population.